2019
DOI: 10.1016/j.heliyon.2019.e02711
|View full text |Cite
|
Sign up to set email alerts
|

Textile finishing dyes and their impact on aquatic environs

Abstract: In the present review, we have been able to describe the different families of dyes and pigments used in textile finishing processes (Yarns, fabrics, nonwovens, knits and rugs) such as dyeing and printing. These dyes are reactive, direct, dispersed, indigo, sulphur and vats. Such that their presence in the liquid effluents resulting from the textile washing constitutes a serious risk, in the absence of their purification, for the quality of receiving aquatic environments. Indeed, the presence of these dyes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
208
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 578 publications
(266 citation statements)
references
References 86 publications
1
208
0
17
Order By: Relevance
“…Azo dyes are the most used dyes and account for more than 60 % of total dyes [2,3]. Approximately 70 % of all the dyes used in industry are azo dyes [4,5]. These compounds are characterized by the functional group (-N¼N-) uniting two symmetrical and/or asymmetrical identical or non-azo alkyl or aryl radicals [6].…”
Section: Introductionmentioning
confidence: 99%
“…Azo dyes are the most used dyes and account for more than 60 % of total dyes [2,3]. Approximately 70 % of all the dyes used in industry are azo dyes [4,5]. These compounds are characterized by the functional group (-N¼N-) uniting two symmetrical and/or asymmetrical identical or non-azo alkyl or aryl radicals [6].…”
Section: Introductionmentioning
confidence: 99%
“…Their irresponsible and incessant dumping into receiving water bodies is claimed to cause a burden to the environment and human health [ 4 ]. These environmental threats range from smell and taste alterations in water sources [ 5 ], abstraction of sunlight in aquatic medium resulting subsequently in dissolved oxygen fall, to their low bio-degradability tendency or their partial degradation giving rise to new intermediates products such as aromatic amines, azo or sulfur compounds which are more toxic than the original mother molecules [ 6 ]. Bearing in mind the acute environmental and health risks, dye molecules have to be removed before being poured into receptor media.…”
Section: Introductionmentioning
confidence: 99%
“…The textile industry has developed rapidly in developing countries in recent years which has led to increasing concerns of textile wastewater pollution. Textile wastewater generally contains various chemicals such as dyes (i.e., azo dyes, triphenylmethanes dyes anthraquinone dyes, nitroseds dyes, xanthenes dyes, phthalocyanines dyes, polymethine dyes, and indigoids) and inorganic compounds (metals) (Berradi et al, 2019). The features of high color density, high concentration of recalcitrant organics and pH, high salinity, and turbidity make textile wastewater one of the most heavily contaminated waters to be treated.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also investigated the kinetics of dye adsorption using this natural material. Berradi et al (2019) provided a summary of various dyes and pigments (indigo, dispersed, reactive, sulfur, and vats) used in textile manufacturing processes and discussed their potential impact on the environments. The authors indicated that the majority of the dyes belong to azo groups which typically feature high stability and pose carcinogenic effects on the environmental ecosystems.…”
Section: Introductionmentioning
confidence: 99%